The Effect of PowerPoint Media on the Learning Outcomes of Elementary School Students in Social Studies subjects - Syamsuriyanti Syamsuriyanti; Nurfaega Nurfaega; Muhammad Nawir (Institut Agama Islam Negeri Palopo, 2021)
This study aims to determine the effect of PowerPoint media on the learning outcomes of elementary school students in social studies subjects. This research was conducted at the State Elementary School 118 Maros Regency with fourth-grade students. Sampling using a purposive sampling technique. Data collection techniques used in this study were observation, tests, and documentation. The hypothesis will be tested using paired sample t-test. The pre-test results showed that the average score obtained by the fourth graders was 9.69, while the post-test showed a score of 14.57. Hypothesis H1 is accepted, and Ho is rejected based on the test results. Thus, the research hypothesis is that there is an influence of PowerPoint media on the learning outcomes of elementary school students in social studies subjects.